Pengaruh Ketimpangan Distribusi Pendapatan Terhadap Persentase Penduduk Miskin Di Provinsi Banten Tahun 2000-2012 - Saraswati, Sri (Journal of Economics & Business UBS, 2020)
Poverty has always been a problem in every developing country, even in developed countries. In Indonesia, the high number of poor people is influenced by various factors, including the existence of inequality in the distribution of both per capita income between one provinces to another. This study aims to analyze how many influence the Gini Index and Williamson Index to the percentage of poor people in the province of Banten in 2000 - 2012. The method of analysis in this study using multiple linear regression analysis with the method of ordinary least squares (OLS). With the help of software Eviews 4.1. The results of this study indicate that the variable distribution of per capita income inequality (Gini index) is influencing positively and it gives a significant impact on the percentage of poor people in the province of Banten, while inequality of income distribution among districts / cities Williamson index does not affect the percentage of poor people in the province of Banten in 2000 - 2012.